Practicality of Guided Inquiry Learning Devices Using Google Sites Media on Static Fluid Materials - Supartin Supartin; Trisnawaty Junus Buhungo; Asri Arbie; Furqon Sanjaya; Meilan Demulawa (Jurnal Penelitian Pendidikan IPA, 2023)
This study aimed to describe the practicality of physics learning devices with guided inquiry learning models using google site media. This research was conducted at SMAN 1 Tilango, and the study sample was class XI IPA, using a simple random sampling technique. This development study uses research and development research (R&D) using the developed ADDIE development model. It will be implemented in class XI IPA of SMA Negeri 1 Tilango for odd quarters of the 2022/2023 Academic Year in determining research topics using simple sampling methods. The results showed that the guided inquiry learning model with google sites media on static fluid material was very well used in the learning process, with an average percentage of learning implementation of 91.2%, an average student response of 83.6%, and an average response of teachers by 92.03%. Results from the average percentage of teacher and student responses on learning tools are expanded into practical categories that can be applied to the learning process.